Using Technology-Supported Transfer of Care Systems: Informing Good Practice Recommendations - Robert James; Efi Mantzourani; Cheryl Way; Alistair Gray; Melissa Burnley; Karen Hodson (MDPI AG, 2021)
The Discharge Medicines Review (DMR) referral system, Refer-to-Pharmacy (RTP), PharmOutcomes and Help for Harry are UK transfer of care systems that aim to reduce the risks associated with hospital discharge. These systems use technology to facilitate the transmission of discharge information to community pharmacy, allowing community pharmacists to provide an adherence-support service. Despite the evidence that these systems benefit patient safety, there is a paucity of literature on their use. This study aimed to describe, compare and contrast these systems to highlight areas that could inform good practice recommendations. A rapid literature review was completed, and from the twenty-six sources of literature that were synthesised, three themes were identified for further exploration in semi-structured interviews with key informants: implementation, system attributes and stakeholder engagement. The key informants were purposively sampled for their role in the development and/or strategic implementation of each transfer of care system (n = 4). Audio recordings were transcribed ad verbatim and analysed both deductively and inductively. One interview was undertaken for each of the DMR, RTP and PharmOutcomes systems. Although all systems shared the same aim, differences were identified such as automated feedback for referrals, marketing strategies and practitioner accountability. Good practice recommendations suggested in this study could be applied to the future development of such systems.